2002
DOI: 10.1046/j.1365-2516.2002.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Radial artery mycotic pseudoaneurysm in a haemophiliac: a potentially fatal complication of arterial catheterization

Abstract: We present a case of radial artery pseudoaneurysm formation in a haemophiliac patient, which developed after radial artery cannulation. Haematologists and anaesthetists should be aware of this potentially fatal condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Despite recommendations to use the radial artery as the first cannulation site in neonates and children, there are reports of serious complications in adult patients associated with indwelling radial artery catheters (19–21). Sellden et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recommendations to use the radial artery as the first cannulation site in neonates and children, there are reports of serious complications in adult patients associated with indwelling radial artery catheters (19–21). Sellden et al.…”
Section: Discussionmentioning
confidence: 99%
“…Fields et al [5] reported the case of an infant who developed a radial artery pseudoaneurysm following arterial puncture and was subsequently diagnosed with haemophilia. Harkin et al [6] reported the case of radial artery pseudoaneurysm formation in a haemophiliac patient, which developed after radial artery cannulation.…”
Section: Handmentioning
confidence: 99%
“…Many small postcatheterization pseudoaneurysms tend to spontaneously thrombose over time . However, large pseudoaneurysms which do not thrombose spontaneously, should be treated, because potential complications of RAP may be nearby venous compression, thromboembolism and rupture with significant bleeding requiring urgent surgery . Until recently, the standard technique of treatment has been surgical repair including radial artery ligation, patch angioplasty using vein segment, RAP ligation and excision with end‐to‐end anastomosis .…”
Section: Discussionmentioning
confidence: 99%